AEMPLOYING QUESTION â ANSWER RELATIONSHIPS (QAR) TO ENHANCE STUDENTSâ READING COMPREHENSION (A CLASSROOM ACTION RESEARCH AT THE FOURTH SEMESTER OF ENGLISH DEPARTMENT STUDENTS OF WIDYA DHARMA UNIVERSITY KLATEN IN THE 2016/2017 ACADEMIC YEAR) - Sholihah, Umi; Anisa, Ike (MAGISTRA, 2017)
In teaching-learning reading, in order to know whether students comprehend what they read,teacher can ask them to answer reading comprehension questions. It may be an indication that students havelow ability of reading if they cannot answer questions correctly. Considering the reason above, the researcheris interested in implementing question-answer relationships (QAR) as a strategy of reading comprehensionproposed by Rafael (1986).The objective of the research is to identify whether QAR can enhance studentsâ reading comprehension..This research is classroom action research on improving studentsâ reading comprehension using QAR thatinvolved three cycles. The subject of the research is the fourth semester students of English Department ofWidya Dharma University Klaten. In data collecting, the research involved two sorts of data: quantitative dataand qualitative data. The quantitative data is gained from test: pre- and post test. After analyzing the scores ofthe written test, the researcher uses a statistical technique to find mean score of the students. For collectingqualitative data, the researcher employed observation, recording/questionnaire, and interview. In analyzingqualitative data, the researcher makes use of interactive model proposed by Miles & Huberman (1984: 21-23),they are data reduction, data display, and data verification.The findings of this research reveal that there are the improvement of studentsâ reading comprehensionskill, participation, and motivation.. The QAR framework gives practice for students to be asked to respond toquestions in the text.Key Words: English textbook, syllabus, 2013 Curriculum